Sistemática y biogeografía de la sección Casparya (Begonia, Begoniaceae) (2017)
In this dissertation, I propose that integration of phylogenetic, biogeographical and climatic trends may help to understand ecological patterns of diversity. For example, the lack of correspondence between the phylogenetic and niche divergences in a mid-Andean centered group: the environmental niche is not more different for phylogenetically distant species than for close related ones. Based on the previous framework, I evaluate hypotheses on the dynamics of net rates of diversification, the link between spatial, climatic niche and phylogenetic relationships and the evolutionary change in morphological characters and their implications for taxonomy. I used as study system the genus Begonia, but the conclusions probably may apply to Other plant groups with a similar biology and distribution. Specifically, I used the principal (in term of richness and distribution) American clade of Begonia, and the sections Casparya, depending on the research question